2010
DOI: 10.1016/j.jbiomech.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical models of helical superstructures in ligament and tendon fibers predict large Poisson's ratios

Abstract: Experimental measurements of the Poisson's ratio in tendon and ligament tissue greatly exceed the isotropic limit of 0.5. This is indicative of volume loss during tensile loading. The microstructural origin of the large Poisson's ratios is unknown. It was hypothesized that a helical organization of fibrils within a fiber would result in a large Poisson's ratio in ligaments and tendons, and that this helical organization would be compatible with the crimped nature of these tissues, thus modeling their classic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 37 publications
5
98
0
Order By: Relevance
“…In this study, we observed a significant decrease in rotation after FL in samples from young horses, suggesting that FL causes alterations to the helix structure. This is somewhat supported by the trend for decreased Poisson's ratios observed in samples from young horses; while the large Poisson's ratios observed may be owing to exudation of fluid from the fascicles [17], finite-element modelling has shown that the presence of helical substructures within tendon predicts large Poisson's ratios [45]. While the specific alterations that occur to the helix during FL are as yet unknown, it is possible that some of the characteristic sample lengthening observed during creep may occur as a result of straightening of the coil of the helix, such that helix pitch angle decreases.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we observed a significant decrease in rotation after FL in samples from young horses, suggesting that FL causes alterations to the helix structure. This is somewhat supported by the trend for decreased Poisson's ratios observed in samples from young horses; while the large Poisson's ratios observed may be owing to exudation of fluid from the fascicles [17], finite-element modelling has shown that the presence of helical substructures within tendon predicts large Poisson's ratios [45]. While the specific alterations that occur to the helix during FL are as yet unknown, it is possible that some of the characteristic sample lengthening observed during creep may occur as a result of straightening of the coil of the helix, such that helix pitch angle decreases.…”
Section: Discussionmentioning
confidence: 77%
“…For collagen in bovine pericardium, at low strain, the Poisson's ratio appears to have a very high value (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), but for strain above 0.09, the Poisson's ratio is in the range 2.1-2.8. For the total strain (from 0 to 0.25), the change in d-spacing and diameter gives 0 ÂŒ 2.1 6 0.7 (these values of 0 can be calculated from Fig.…”
Section: Resultsmentioning
confidence: 95%
“…15,16 Modeling of the crimp present in many collagen tissues, such a tendon and ligament or helical structure of the fibrils, has suggested that these features could explain much of the high Poisson's ratio of the tissue composed of collagen. 17 It has also been suggested that in tendon, the strain may be taken up by sliding of fibrils within the tendon rather than by extension of the collagen fibrils. 18 In leather, where there is very little crimp, the reorientation of fibrils may be an important mechanism for absorbing strain.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the presence of a helical organization within the fascicle. Micromechanical models of helical structures within tendon and ligament suggest the presence of helical twisting, which may be responsible for the large experimentally observed Poisson's ratios [33]. Evidence for helical organization has been reported in histological studies on tendon and ligament [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%